Temperature-influenced Bulk Emulsion (BE) Demulsification Method as a PIBSA-MEA Emulsifier Durability Test in Blasting Environments under 100 °C - Gunaryo; Budiman, Anggito; Widyawati, Ratihlia Dhea; Salsabila, Fidela Aurellia; Gibran, Syahdan Al; Maharani, Anggaria (Indonesian Journal of Chemical Studies, 2024)
This research attempts to provide a better method, examine more effective temperatures for testing emulsifiers, and determine the demulsification limit that indicates emulsifier durability. This experiment was conducted by varying the temperature (40, 60, 80, and 100 °C) for heating the product with a test time of 1, 2, 4, and 6 h, then detected using formaldehyde titration to determine the highest level of demulsification of ammonium nitrate (AN) salt at each temperature in the product. The results showed that 100 °C was the most effective and representative temperature for testing the durability of the emulsifier with the highest level of demulsification from the other temperatures. This was indicated by the weight of AN salt that came out of the emulsion reaching 2.05 g from 20 g of emulsion or about 10.25% of the total weight of the product within 6 h. Emulsifiers with AN levels below 2.05 g (10.25%) were considered to pass the test and could be used for further production or analysis. This new test method was expected that bulk emulsion manufacturers would be faster in eliminating PIBSA-base (Polyisobutylene succinic anhydride-base) emulsifier products widely used by emulsifier manufacturers in manufacturing BE. This was due to it only focusing on the ability of emulsifiers to hold the product in high-temperature exposure so that it remained unified and not demulsified.